Coffee intake (Coffea arabica L.) reduces advanced glycation end product (AGEs) formation and platelet aggregation in diabetic rats - Alessandra dos Santos Danziger Silvério; Rosemary Gualberto Fonseca Alvarenga Pereira; Stella Maris da Silveira Duarte; Sônia Aparecida Figueiredo; Fernanda Borges de Araújo Paula; Tomaz Henrique Araújo; Cláudia de Souza Ferreira; Bruno César Corrêa Salles; André Luiz Machado Viana; Eric Batista Ferreira; Maria Rita Rodrigues (São Paulo State University (UNESP), 2021)
Objectives: The study aimed to determine the effect of coffee intake on AGEs formation and platelet aggregation in diabetic Wistar rats. Methods: Coffee powder samples were used to prepare a 10% beverage. Diabetes mellitus was induced in the animals by administering 2% alloxan. All animal experiments were approved by the ethics committee for animal experiments under N°. 420/2012 and 536/2013. Diabetic and non-diabetic rats were divided into 6 groups treated and untreated with coffee (7.2 mL/Kg body weight) and aminoguanidine (AGE inhibiting agent) (100 mg/Kg body weight) for 50 days. After 50 days, the animals were fasted for 12 h and anesthetized (40 mg/Kg sodium pentobarbital) intraperitoneally. Blood samples were collected from the abdominal artery puncture. Hematological parameters (red cells, hemoglobin, hematocrit and leukocyte) and glycemic and HbA1c levels were measured. AGEs quantification (spectrofluorometric method) and the platelet aggregation test (aggregation of cuvettes in a four-channel platelet aggregometer) were also conducted. The rats' renal function was evaluated by measuring serum urea and creatinine. Results: Data showed that coffee intake had no effect on the hematological parameters. Fasting glucose and HbA1c dosage were significantly higher in diabetic animals compared to non-diabetic animals (confirmed the effectiveness of inducing and maintaining diabetic status). Results showed that coffee reduced AGE formation and platelet aggregation in our animal model, not altering the animals' renal function. Conclusions: These results suggest beneficial effects on vasculopathy, a common complication in diabetic patients.